In Vitro Differentiation of Embryonic Stem Cells Into Cardiac-Like and Neuronal-Like Cells - Paz, Ana Helena da Rosa; Lugo, Ana Ayala; Terraciano, Paula Barros; Meurer, Luise; Passos, Eduardo Pandolfi; Lima, Elizabeth Cirne (Clinical and Biomedical Research, 2008)
Embryonic stem cells are pluripotent cell lines with the capacity of self-renewal and a broad differentiation plastic-ity. They are isolated from preimplantation embryos and can be cultured in vitro for long time without losing their pluripo-tency. Embryonic stem cells can also differentiate in vitro with the proper combination of growth and differentiation fac-tors, cells will differentiate into more advanced stages of embryogenesis generating different adult cell type. In the pre-sent study, we induced the in vitro differentiation of mouse embryonic stem cells (line R1) into cardiomyocytes and neu-ronal cells. These differentiations were evaluated by reverse transcription-polymerase chain reaction to verify presence of tissue-specific markers.